Hegemonic Masculinity: Rethinking the Concept - Connell, R. W.; Messerschmidt, James W. (Gender & society, 2005)
The concept of hegemonic masculinity has influenced gender studies across many academic fields but has also attracted serious criticism. The authors trace the origin of the concept in a convergence of ideas in the early 1980s and map the ways it was applied when research on men and masculinities expanded. Evaluating the principal criticisms, the authors defend the underlying concept of masculinity, which in most research use is neither reified nor essentialist. However, the criticism of trait models of gender and rigid typologies is sound. The treatment of the subject in research on hegemonic masculinity can be improved with the aid of recent psychological models, although limits to discursive flexibility must be recognized. The concept of hegemonic masculinity does not equate to a model of social reproduction; we need to recognize social struggles in which subordinated masculinities influence dominant forms. Finally, the authors review what has been confirmed from early formulations (the idea of multiple masculinities, the concept of hegemony, and the emphasis on change) and what needs to be discarded (one-dimensional treatment of hierarchy and trait conceptions of gender). The authors suggest reformulation of the concept in four areas: a more complex model of gender hierarchy, emphasizing the agency of women; explicit recognition of the geography of masculinities, emphasizing the interplay among local, regional, and global levels; a more specific treatment of embodiment in contexts of privilege and power; and a stronger emphasis on the dynamics of hegemonic masculinity, recognizing internal contradictions and the possibilities of movement toward gender democracy.